EPISTEMOLOGI ILMU PERSPEKTIF MULLĀ ṢADRĀ DAN RELEVANSINYA TERHADAP PENGALAMAN INTUITIF - Kerwanto (Jurnal An-Nufus, 2022)
This article explores the basic tenets of Mullā Ṣadrā's philosophical epistemology. The important value of this study is the critique of Western epistemology which ignores metaphysics as an approach and study in epistemology. Through this article, the author wants to show the unique characteristics of Mullā Ṣadrā's epistemological structure, which makes ontology the basis of epistemology. Mullā Ṣadrā makes the knowledge of presence (ilm huḍūrī) the basis for the validity of the truth of intuitive experience. Thus, intuitive experiences that are rejected by some can be justified. In addition, in this article, the author also describes several other unique discussions that distinguish Mulla Ṣadrā's thoughts from other philosophers, such as: the unique definition of knowledge, the relationship between the subject and object of knowledge and the link between the motion of substance (al-ḥarakah al-jauhariah) with knowledge.